Steelstriker - Lu, Marie, 1984- (Skyhunter, 2021)
"With her friends scattered by combat and her mother held captive by the Premier, Talin is forced to betray her fellow Strikers and her adopted homeland. She has no choice but to become the Federation's most deadly war machine as their newest Skyhunter."--